THE EFFECT OF CELEBRITY DIPLOMACY: PRELIMINARY STUDY ON THE IMPACT OF CLIMATE CHANGE CAMPAIGN BY BLACKPINK TOWARDS BLINK INDONESIA COMMUNITY (BOI) - Widyawati, Widyawati; Gunawan, Aditya Batara (JWP (Jurnal Wacana Politik), 2023)
This study aims to explore the impact of climate change campaign by Blackpink towards the Blink Official Indonesia (BOI) community. Currently, the modern diplomacy practice is no longer focusing on the state actor but more importantly, involving non-state actor, especially public figures or celebrities as the ambassador to carry out specific mission of the states or international organizations at the global level. An example of such development is the appointment of South Korea-based music group Blackpink as the goodwill ambassador for the United Nations Climate Change Conference 26 (COP 26) in 2021. The selection of Blackpink as the COP26 ambassador was intended to improve awareness on the global campaign against climate change, especially within the BLINK – Blackpink fans community – worldwide through #ClimateActionInYourArea campaign in the Blackpink official Youtube account. This study used a survey method of 203 sample respondents from a population of followers from BOI accounts on Instagram using probability sampling technique. The analysis results show that Blackpink’s celebrity diplomacy campaign encourages Blink Indonesia to develop interest in climate change issues by making donations and emphasizing the importance of climate action in their neighborhood. Such findings confirm the expected effect of attraction tactic of soft power strategy in the current diplomatic practice, that is to co-opt the perception of targeted audience towards specific issue in international relations.